Performance Comparison of Fuzzy Mamdani and Sugeno in Curtain and Lighting Control - M. Alung Chaiyura Chanpal; Daniel Indra Saputra Manurung; Daniel Sutopo Pamungkas (Journal of Applied Electrical Engineering, 2025)
Efficient room lighting is essential for user comfort and health. This study implements and compares Fuzzy Mamdani and Sugeno methods in an automatic curtain and lighting control system based on Arduino Uno. The system responds to light intensity changes by adjusting curtains and a dimmable lamp according to LDR sensor values. Tests were conducted under various conditions to evaluate performance. Results show that Sugeno has a faster average response time of 13,898 seconds compared to Mamdani's 15,158 seconds, with a difference of 1,26 seconds. Sugeno also demonstrates better accuracy: for curtain control, it achieved MSE of 347,9368872 and RMSE of 18,65306643, while Mamdani recorded MSE of 570,71862 and RMSE of 23,889718. For dimmer control, Sugeno obtained MSE of 1683,99071 and RMSE of 41,0364559, outperforming Mamdani's MSE of 2679,24 and RMSE of 51,7614. This implementation provides an optimal solution for automatic lighting management to enhance energy efficiency and user comfort.